Peran Layanan BK Dalam Meningkatkan Kedisiplinan Santriwati di Ponpes Hikmatusysyarief NWDI Salut - S, Zulpa (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2024)
ABSTRACT The formulation of the problem in this research is how the role of guidance and counseling services plays in improving female students' discipline in the Hajjah Mulhatun Zahid girls' dormitory and what are the supporting and inhibiting factors for implementing guidance and counseling services in the Hajjah Mulhatun Zahid girls' dormitory. The aim of this research is to determine the role of guidance and counseling services in improving the discipline of female students and to determine the supporting and inhibiting factors in the implementation of guidance and counseling services. This type of research is phenomenological research with a descriptive qualitative approach. The data collection techniques used in this research are observation, interviews and documentation. Based on the research results obtained from the sources, it can be concluded that the role of guidance and counseling services implemented in the Hajjah Mulhatun Zahid girls' dormitory has a very big impact and influence on improving female students' discipline. The supporting factors for the implementation of guidance and counseling services are data instrumentation, case conferences and home visits, and the inhibiting factors are the lack of guidance staff in schools and the lack of technical guidance capabilities in dormitories.Keywords: Guidance and Counseling Services, Discipline